A tale of two chitons: is habitat specialisation linked to distinct associated bacterial communities?. Issue 3 (17th October 2012) - Duperron, Sébastien; Pottier, Marie‐Anne; Léger, Nelly; Gaudron, Sylvie M.; Puillandre, Nicolas; Le, Stéphanie; Sigwart, Julia D.; Ravaux, Juliette; Zbinden, Magali
Abstract Although most chitons (Mollusca: Polyplacophora) are shallow‐water molluscs, diverse species also occur in deep‐sea habitats. We investigated the feeding strategies of two species, Leptochiton boucheti and Nierstraszella lineata, recovered on sunken wood sampled in the western Pacific, close to the Vanuatu Islands. The two species display distinctly different associations with bacterial partners. Leptochiton boucheti harbours Mollicutes in regions of its gut epithelium and has no abundant bacterium associated with its gill. Nierstraszella lineata displays no dense gut‐associated bacteria, but harbours bacterial filaments attached to its gill epithelium, related to the Deltaproteobacteria symbionts found in gills of the wood‐eating limpet Pectinodonta sp. Stable carbon and nitrogen isotope signatures and an absence of cellulolytic activity give evidence against a direct wood‐feeding diet; both species are secondary consumers within the wood food web. We suggest that the distinct associations with bacterial partners are linked to niche specialisations of the two species. Nierstraszella lineata is in a taxonomic family restricted to sunken wood and is possibly adapted to more anoxic conditions thanks to its gill‐associated bacteria. Leptochiton boucheti is phylogenetically more proximate to an ancestral form not specialised on wood and may itself be more of a generalist; this observation is congruent with its association with Mollicutes, a bacterial clade comprising gut‐associated bacteria occurring in several metazoan phyla.